Level of Public Knowledge Regarding The Transmission and Prevention of Dengue Fever in The Working Area of The Matsum City Public Health Center, Medan - Jacky Zakaria Alfiani; Aulia; Zaim Anshari; Budi Kurniawan (International Journal of Public Health Excellence (IJPHE), 2026)
Introduction: Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia. Insufficient public knowledge about transmission and prevention contributes to high disease incidence. Objective: This study aimed to assess the level of community knowledge regarding DHF transmission and prevention in the working area of Puskesmas Kota Matsum, Medan Area District. Methods: An analytic survey with a cross-sectional design was conducted involving 98 respondents who had previously experienced DHF. Data were collected using structured questionnaires and analyzed using univariate and bivariate analysis. Results: Most respondents were female (56.1%) and aged 26–35 years (51.0%). Approximately 53.0% had good knowledge of DHF. A significant relationship was found between knowledge level and DHF prevention behavior (p < 0.05). Conclusion: Community knowledge is significantly associated with DHF prevention. Continuous health education is needed to reduce DHF incidence in the Puskesmas Kota Matsum area